Diagnostika topih poškodb trebuha - Komadina, Radko (Medicinski razgledi, 1999)
Modern traumatology uses scoring systems to determine the efficiency of treatment. Surgeons employ a variety of diagnostic modalities for the assessment of blunt abdominal trauma, the choice of the modality depending on the severity of general status of the critically injured patient. Ninety-nine severely injured patients, included in the 3-year Slovenian Society of Trauma Surgeons Protocol of Severely Traumatised, were laparotomised because of blunt abdominal trauma. A retrograde analysis was used to determine the impact of the severity of trauma, as defined by the Revised Trauma Score (RTS)and the Injury severity score (ISS), on the diagnostic modality used to assess blunt abdominal trauma prior to undertaking laparotomy. The average ISS value was statistically significantly lower in patients with a positive ultrasonic diagnosis than in patients with a positive diagnostic peritoneal lavage (p<0,003). The average RTS value was significantly higher in patients with a positive ultrasound than in patients with positive results of diagnostic peritoneal lavage (p<0,02). To save them time, surgeons evaluated gravely affected patients with severe abdominal trauma who had low RTS and high ISS scores by diagnostic peritoneal lavage which was performable simultaneously with the resuscitation procedure. Patients with clinically suspected blunt abdominal trauma, showing higher RTS and lower ISS scores were evaluated by ultrasound.
Keywords: Poškodbe, tope; Wounds, nonpenetrating; Trebuh, poškodbe; Diagnosis; Abdominal injuries; Poškodbe, točkovanje; Injury severity score; trebuh; poškodbe; Diagnostika; travmatologija